An analysis of hospital efficiency and productivity growth using the Luenberger productivity indicator - Carlos Pestana Barros; António Gomes de Menezes; José António Cabral Vieira; Nicolas Peypoch; Bernardin Solonandrasana (Institute for the Study of Labor (IZA), 2007)
We analyze the efficiency and productivity growth of a representative sample of Portuguese hospitals from 1997 to 2004, using an innovative approach by employing the directional distance function and the Luenberger productivity indicator. The primary advantage of our approach is that both input contractions and output expansions are considered. Our model generates a productivity indicator that is decomposed into the usual constituents of productivity growth: technological change and efficiency change. The results show that, on average, Portuguese hospitals did not experience productivity growth during the period analyzed. In addition, the incidence of positive productivity growth across Portuguese hospitals was remarkably low.
urn:nbn:de:101:1-20080410283
Keywords: 330; Krankenhaus; Produktivität; Technische Effizienz; Portugal